The Benedictine Culture of Medieval Iceland - Clark, James G. (Religions, 2023)
The monastic tradition of St Benedict of Nursia inspired and influenced Iceland’s medieval monasteries. Four communities, two each of men and women, which were identified in contemporary records as ‘under the rule of Saint Benedict’, endured for four hundred years, until the Protestant suppressions of the mid-sixteenth century. The monasteries of men emerged as Iceland’s most important centres of literary production; each of the churches was the focus of public worship and popular cults, and at times in their history, they may also have maintained the largest monastic populations seen in the island. With no visible trace of their physical environment, material evidence only now being revealed in excavations and very few documentary records describing their form of Benedictinism, their observant customs and broader Benedictine culture remain elusive. Drawing on the inventories (máldagar) of their property made at intervals between the thirteenth and sixteenth centuries, together with the representation of their regular life in contemporary biskupa sögur, this paper reveals a monastic practice that did diverge from that of Benedictines elsewhere in northern Europe but that nonetheless expressed a powerful attachment to some of the principal ideals of the Benedictine Rule: abbacy, conventual fraternity and the interplay of contemplative and active occupation. Above all, these communities appear to have propagated a cult interest in the figure of Benedict himself, placing him at the centre of their worship life long after Benedictines elsewhere in Europe had allowed him to be eclipsed by national and regional cults of more recent creation.